Digital Skills Enhancement For MSMEs In The Digital Economy Era - Azuwandri, Azuwandri (Jurnal Pengabdian Mandiri, 2024)
This research addresses the importance of digital upskilling for Micro, Small and Medium Enterprises (MSMEs) in the digital economy era. By analysing the impact of digital skills training programmes on MSMEs, the study identifies their benefits in improving operational efficiency, expanding markets and increasing competitiveness. Implementation challenges such as resource constraints and resistance to change are also highlighted. Taking into account the success of existing programmes and strategic recommendations to support MSMEs, the study concludes that investment in digital skills is a crucial step to ensure sustainable growth and adaptation of MSMEs in the dynamic digital era. It is hoped that these findings can provide guidance for public policies and government strategies in supporting the overall digital transformation of MSMEs.